Hepatitis C knowledge among gay and other homosexually active men in Australia. (15th September 2015) - Lea, Toby; Hopwood, Max; Aggleton, Peter
Abstract: Introduction and Aims: Gay and other homosexually active men (hereafter 'gay men') are at elevated risk of becoming infected with hepatitis C virus (HCV) via injecting drug use and sexual risk practices. This paper aimed to measure HCV knowledge among gay men in Australia and whether knowledge differed according to HCV risk. Design and Methods: In 2013, a cross‐sectional, online survey of 405 Australian gay men explored the social aspects of HCV. Bivariate and multivariate linear regressions were used to examine factors associated with higher HCV knowledge. Results: The mean age of respondents was 39.2 years (SD = 13.3), and most men (75.3%) were born in Australia. According to self‐report, 32.1% were HIV‐positive, 3.0% were HCV‐positive and 8.9% were HIV/HCV co‐infected. The mean number of correct HCV knowledge items was 8.2 (SD = 3.9; range 0–15). In a multivariate analysis, higher HCV knowledge was associated with higher educational attainment, being HCV‐positive, being HIV‐positive and injecting drug use. Discussion and Conclusions: HCV knowledge among gay men was moderately good, although knowledge of testing, treatment and natural history of HCV was generally quite poor. Encouragingly, higher knowledge was reported among men at highest HCV risk. Viral hepatitis and HIV organisations, together with general practitioners and other health services, should continue to target gay men at a high risk of acquiring HCV with education and health promotion. [Lea T, Hopwood M, Aggleton P. Hepatitis C knowledge among gay and other homosexually active men in Australia. Drug Alcohol Rev 2016;35:477–483]